The Relationship Between Power Structure of Man-Powered in the Family and Family Function - محمد زارعی توپخانه; مسعود جان‌بزرگی; محمدرضا احمدی (فصلنامه خانواده پژوهی, 2015)
This study seeks to examine the relationship between family power structure of man-powered and the family function. The sample consisted 170 teachers selected by cluster samp-ling method that is in Nurabad city, Lorestan. In this research, FAD 45-item questionnaire of family functioning and 36-item questionnaire of family power structure were used. This research represents a quantitative correlation. The Data were analyzed by Pearson correlation and stepwise multiple regression. The research findings showed a significant positive relationship between family power structure of man-powered and family function style (general function of family, emotions, problem solving), but the relationship between the power structure of man-powered and role was not significant. Furthermore, the power structure (How to apply power), as far as male authority in family is concerned, explained approximately %10 of the variance of family function. Accordingly, Male authority strengthened family function.